2014
DOI: 10.1002/2014jd021588
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of decadal global water vapor changes derived from independent satellite time series

Abstract: Citation:Mieruch, S., M. Schröder, S. Noël, and J. Schulz (2014), Comparison of decadal global water vapor changes derived from independent satellite time series, J. Geophys. Res. Atmos., 119, 12,489-12,499, doi:10.1002 Abstract We analyze trends in total column water vapor (TCWV) retrieved from independent satellite observations and retrieval schemes. GOME-SCIAMACHY (Global Ozone Monitoring Experiment-SCanning Imaging Absorption spectroMeter for Atmospheric CHartographY) measurements are carried out in the v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 42 publications
3
29
0
Order By: Relevance
“…Significant negative (drying) trends are observed in south-tropical eastern Pacific region, west of the United States and generally south of 60°S. The dipole structure in the south-eastern tropical Pacific area is consistent with the findings of Mieruch et al (2014) and 25 is due to the different ENSO phases for this time period, as reported by Trenberth et al (2005). Over land, significant positive trends are observed in equatorial region along the ITCZ, especially in northern South America, Central Africa, and Indonesia, and in the northern hemisphere, especially over northern North America, Greenland, most of Europe and Siberia.…”
Section: Trends In Gps and Era-interim Iwv (1995-2010) 20supporting
confidence: 89%
“…Significant negative (drying) trends are observed in south-tropical eastern Pacific region, west of the United States and generally south of 60°S. The dipole structure in the south-eastern tropical Pacific area is consistent with the findings of Mieruch et al (2014) and 25 is due to the different ENSO phases for this time period, as reported by Trenberth et al (2005). Over land, significant positive trends are observed in equatorial region along the ITCZ, especially in northern South America, Central Africa, and Indonesia, and in the northern hemisphere, especially over northern North America, Greenland, most of Europe and Siberia.…”
Section: Trends In Gps and Era-interim Iwv (1995-2010) 20supporting
confidence: 89%
“…Although only lag 1 is considered explicitly, further autocorrelations at higher lags are also considered implicitly, since the correction approach is based on autoregressive processes of order 1 (AR[1]) (Thiebaux and Zwiers, 1984;Mieruch et al, 2014), whose autocorrelation function decreases exponentially, thus considering also higher lags than 1. For uncorrelated data, the statistical significance on the 10 % level for 25 data points is achieved by a correlation coefficient of |ρ| ≥ 0.33.…”
Section: Metricsmentioning
confidence: 99%
“…Thus, TCWV products from satellite observations in the red spectral range are a valuable complement to MW, IR, and RO water vapor products, which are sensitive only to specific surfaces or altitude ranges. TCWV products derived from GOME, SCIAMACHY, and GOME-2 have already been used to investigate the water vapor evolution over time on a global scale, e.g., the effects of El Niño (Wagner et al, 2005;Loyola et al, 2006) or trends Mieruch et al, 2008Mieruch et al, , 2011Mieruch et al, , 2014.…”
Section: Introductionmentioning
confidence: 99%